HUBUNGAN ANTARA KECERDASAN SPIRITUAL DENGAN KEMAMPUAN COPING STRESS SISWA SMA NEGERI 1 KARANGANYAR DEMAK - Izza, Nurul Baeti; Sutoyo, Anwar (Universitas PGRI Semarang, 2022)
Abstract. this research was holded based on the phenomenon of students pressure and causing stress. Tired to studying online, peers, and homework are some of the pressure.Coping stress can help students. And spiritual intelligence importent to balance that. To achieve this goal, the researcher uses a quantitative technique of correlational research. The aims of this research is to examine the relationship between variables. The sample uses a proportionade random sampling with total of 265 students. Data using spiritual intelligence and coping stress ability scale. Then, the data were analyzed using the product moment correlation. This study obtained the results of the significance value 0,000 0,05 and correlation value of 0,590. This means that there is a positive and significant relationship between spiritual intelligence and coping stress ability students in SMA Negeri 1 Karanganyar Demak. Suggestions for BK teachers can give attention by developing spiritual intelligence to improve stress coping abilities.